Global Dynamics of a Delayed Fractional-Order Viral Infection Model With Latently Infected Cells - Rajivganthi, C.; Rihan, F. A. (Frontiers in Applied Mathematics and Statistics, 2021)
In this study, we propose a fractional-order virus infection model, including latent infection, the Holling type II response function, and a time-delay representing the viral production cycle of infected cells. According to the characteristics equations for the model, certain sufficient conditions that guarantee local asymptotic stability of infection-free, and interior steady states are discussed. A Hopf bifurcation occurs when the time-delay passes through its critical value (threshold parameter). Utilizing LaSalle's invariance principle and Lyapunov functions, we also investigate the global stability of infection-free and interior steady states. Numerical simulations illustrate the effectiveness of the theoretical results.